ACHIEVEMENTS AND PROBLEMS OF ONLINE EDUCATION IN TEACHING FOREIGN LANGUAGES (INTERNATIONAL JOURNAL OF RECENTLY SCIENTIFIC RESEARCHER'S THEORY, 2023)
This article describes the advantages, opportunities and disadvantages of online education in the process of teaching foreign languages. The importance of modern technology in the educational process is discussed.